A Study Of Maslahah Al - Mursalah On Efforts To Legalize Marijuana For Medical Needs In Indonesia In The Aspect Of Legal Exceptions - Nispul Khoiri (Universitas Islam Negeri Sumatera Utara, Medan, 2022)
In this descriptive qualitative study (library research), al-Maslahah Mursalah looks at legal methodology (usul fiqh) in the context of efforts to make medical marijuana legal in Indonesia. It is normative and looks at legal exceptions. The research findings conclude: First, al-Maslahah Mursalah is one of the Islamic legal methodologies appropriately used as an argument for the legalization of marijuana for medical needs in Indonesia, taking into account: (a). Al-Maslahah Mursalah is a real and general maslahah. (b). Judged by common sense as a true maslahah-really in line with the purpose of shara'. (c). Judged by common sense as the ultimate maslahah and having been in line with the objectives of shara' does not clash with the arguments of shara'. (d). Al-Maslahah Mursalah was practised with the narrow conditions of life. Second, the study of al-Maslahah Mursalah on the aspect of legal exceptions to the legalization of marijuana for medical needs in Indonesia is quite open through (a). The process of study and research by representative institutions to find the content of marijuana as an alternative medicine and therapy; if it becomes the only ingredient contained in cannabis content, then legalization can be categorized as an emergency or an exception to the law. The purpose of rukshah is to maintain benefits and reject kemafsadatan. Therefore, according to the scholars of ushul, the law of using rukhshah is permissible /ibahah. (b). Suppose the results of the study find the content of marijuana as an alternative medicine and therapy. In that case, it becomes the basis for disclosing the value of the legalization of marijuana for medical purposes. The values of benefit will create the fulfilment of basic human needs consisting of the maintenance of religion, the maintenance of reason, the maintenance of property, the maintenance of the soul, and the maintenance of offspring/honour.